1998
DOI: 10.1542/peds.101.5.865
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory Evoked Potentials in Very Preterm Infants in Relation to l-Thyroxine Supplementation

Abstract: L-Thyroxine supplementation during the first 6 weeks of life did not decrease cortical N1 peak latency in infants of <30 weeks' gestational age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In younger preterm infants the responses are delayed and prolonged in duration, probably due to a slower conduction velocity due to immature myelination (Klimach and Cooke, 1988a;Taylor et al, 1996;Smit et al, 2000). The latencies decrease rapidly towards term (Hrbek et al, 1973;Karniski et al, 1992;Smit et al, 1998), but delayed maturation of sensory pathways has been suggested on the basis of longer latencies of the N1 at term in preterm infants compared with fullterm infants (Smit et al, 2000). However, this finding was not corroborated in another study (Klimach and Cooke, 1988a).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In younger preterm infants the responses are delayed and prolonged in duration, probably due to a slower conduction velocity due to immature myelination (Klimach and Cooke, 1988a;Taylor et al, 1996;Smit et al, 2000). The latencies decrease rapidly towards term (Hrbek et al, 1973;Karniski et al, 1992;Smit et al, 1998), but delayed maturation of sensory pathways has been suggested on the basis of longer latencies of the N1 at term in preterm infants compared with fullterm infants (Smit et al, 2000). However, this finding was not corroborated in another study (Klimach and Cooke, 1988a).…”
Section: Introductionmentioning
confidence: 91%
“…The sensitivity of abnormal median-nerve SEPs to predict CP has ranged from 13 to 100%, with a specificity of 87-100% (Klimach and Cooke, 1988b;Willis et al, 1989;Majnemer et al, 1990;De Vries et al, 1992;Pierrat et al, 1997), whereas respective values for abnormal tibial nerve SEPs have been 63-96% for sensitivity and 50-99% for specificity (White and Cooke, 1994;Pierrat et al, 1997;Pike and Marlow, 2000). Many SEP studies have experienced technical difficulties in reliably recording the responses, particularly in the youngest preterm infants (Klimach and Cooke, 1988a;Smit et al, 1998Smit et al, , 2000. These difficulties probably explain part of the variability in the specificity and sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…These children were evaluated at 6 months to 5.5 years of age (78). Although the treated group showed significantly higher levels of serum T 4 , neurophysiological functioning (71,72) or cognitive abilities were not improved (71,73,74). However, when children were stratified by gestation age, a marked benefit of TH therapy was observed for early neuromotor skills and later cognitive abilities in children born before 27 weeks (72) whereas children born at 28 or 29 weeks showed the opposite effect, performing worse than controls.…”
Section: Maternal Hypothyroidismmentioning
confidence: 99%
“…The infants were tested without sedation, while awake. MNCV and SEP recordings took about an hour to complete, were stored on disk and reassessed later as described earlier (13,14). During follow-up, neurologic development and performance on the Bayley Scales of Infant Development were assessed by a developmental paediatrician and developmental psychologist at 6, 12 and 24 mo of corrected age.…”
mentioning
confidence: 99%